Effect of methylene chain length of perovskite-type layered [NH3(CH2)nNH3]ZnCl4 (n = 2, 3, and 4) crystals on thermodynamic properties, structural geometry, and molecular dynamics. Issue 60 (23rd November 2021) - Lim, Ae Ran
Abstract : 1 H NMR spin–lattice relaxation times T 1 ρ of [NH3 (CH2 ) n NH3 ]ZnCl4 ( n = 2, 3, and 4) as a function of inverse temperature. The solid lines represent activation energy. Abstract : The structure of organic–inorganic perovskite [NH3 (CH2 )4 NH3 ]ZnCl4 was determined; the lattice constants with monoclinic structure were determined to be a = 7.2527 Å, b = 8.1101 Å, c = 10.3842 Å, and β = 80.3436°. The crystal was almost thermally stable up to approximately 560 K. The endothermic peaks at 481 K and 506 K were assigned to the phase transition of the material. In addition, the structural characteristics and molecular dynamics of the cation were studied via magic angle spinning nuclear magnetic resonance experiments. Based on the results, the effects of the length of the CH2 group in the cation of the [NH3 (CH2 ) n NH3 ]ZnCl4 ( n = 2, 3, and 4) crystals were considered. Regardless of whether n was even or odd, the differences in the thermal and physical properties were minimal. Moreover, a difference in molecular motion relative to the length of the cation was observed only at high temperatures. These results provide useful information about the thermal stability and molecular dynamics of [NH3 (CH2 ) n NH3 ]ZnCl4 crystals and are expected to facilitate potential applications of such compounds in supercapacitors, batteries, and fuel cells.